HISTO-ARCHITECTURE OF THE SMALL INTESTINE OF GAROLE SHEEP - R. Malakar; P. Das; A. K. Mandal; M. M. Islam; S. Das; N. Chaudhury (Exploratory Animal and Medical Research, 2023)
Ruminants like sheep are prone to infections through ingestion of contaminated feed and water since they are reared on a free-ranging system. The gut immune system plays a major role in fighting the pathogens that gain entry through the oral route. The present study was conducted to explore the histological organization of the small intestine of the adult Garole sheep as it is the major site of absorption in the intestine. The intestine samples were collected from 10 healthy sheep. Tissues collected from the duodenum, jejunum, and ileum were fixed in a 10% neutral buffered formalin solution and processed for histological studies by following standard protocols. The small intestine revealed four distinct layers namely tunica mucosa, tunica submucosa, tunica muscularis, and tunica serosa inside out. The tunica mucosa consisted of lamina epithelialis, lamina propria with intestinal glands, and lamina muscularis. The tunica mucosa presented numerous villi of different shapes and heights lined by columnar epithelial cells with Goblet’s cells, lymphocytes, Paneth’s cells, etc. interspersed among them. Brunner’s glands were present in the initial portion of the duodenum and Peyer’s patches were observed in the middle ileum.